Low-Code and No-Code in Secondary Education-Empowering Teachers to Embed Citizen Development in Schools - McHugh, Sally; Carroll, Noel; Connolly, Cornelia (Computers in the schools, 2024)
Citizen Development (CD) is a method of delivering low-code no-code (LCNC) development that empowers subject matter experts to design, develop, and deploy applications into production as though they were full-on, experienced coders. This paper explores teachers' perceptions around the potential for, and enactment of LCNC in our education system. Workshops, surveys, and interviews were conducted with in-service teachers. Teachers are open to improving their digital skills. Nevertheless, some teachers fear technology and are reluctant to embrace change. Our results indicate that it is timely to leverage the increased use of technologies in the classroom before teaching reverts to pre-pandemic norms of "face-to-face." CD provides an excellent opportunity to introduce teachers and students to aspects of computer science without placing demands on them to develop technical skills. The paper provides considerations for the adoption of CD in our education system and in initial teacher education programs.